Hydrothermal synthesis of tetragonal and wurtzite Cu2MnSnS4 nanostructures for multiple applications: Influence of different sulfur reactants on growth and properties. (January 2021) - Malik, Javied Hamid; Zaman, M Burhanuz; Poolla, Rajaram; Malik, Khurshaid Ahmad; Assadullah, Insaaf; Bhat, Aadil Ahmad; Tomar, Radha
Abstract: The present article reports the hydrothermal synthesis of quaternary Cu2 MnSnS4 (CMTS) nanostructures under subcritical reaction conditions. The effect of different chalcogen (sulfur) precursor sources (l -cysteine, elemental sulfur and sodium sulfide) on the growth and properties of the nanostructures is studied. The sulfur precursors showed prominent influence on the structural and morphological properties of the nanostructures. Structural properties indicated the growth of single phase crystalline materials. The crystal phase was controlled and determined by the reactivity of the sulfur sources. Metastable wurtzite phase was achieved with the mildly reactive precursor while tetragonal phase was obtained in the case of highly reactive precursors. Morphological studies showed formation of nanoflakes and anisotropic two-dimensional irregular nanostructures. Surface area analysis indicated that the nanoflakes are mesoporous in nature and exhibited a high specific surface area of 32.24 m 2 /g. The electrical studies demonstrated p-type conductivity of the material. Optical properties revealed optimum energy band gap value (~1.7 eV) of the nanostructures, suitable for the solar energy conversion applications. The magnetic properties indicated ferromagnetic behavior of the CMTS nanoflakes. The nanostructures were investigated as catalysts for photocatalytic decolaration of malachite green (MG) dye under UV–Visible light illumination. The nanoflakes showed good activity against the dye and photodegraded 95% of the dye in an illumination duration of 140 min. The photocatalysts exhibited good stability during the photocatalytic processes.